ANALISIS WACANA KRITIS PADA CATATAN NAJWA BERJUDUL “TRIAS KORUPTIKA” PERSPEKTIF NORMAN FAIRCLOUGH - Ummi Habibah, Siti (Adabiyyāt: Jurnal Bahasa dan Sastra, 2020)
practices that consist of representation, identity and social relationships, so it is closely related to the context beyond discourse. One of the Catatan Najwa TV Programs entitled “Trias Koruptika” indicates the ideology in the text affected by the social context when the record was created. This study aims to see the construction of ideology and social context behind the writing of the text. This research is qualitative descriptive research. A theory used is a critical analysis of Norman Fairclough’s perspective that includes analysis in three dimensions: analysis of language text, discourse practice, and socio-cultural practice. The results showed that in text analysis, Catatan Najwa voiced disappointment, criticism and built a negative representation of three government institutions due to a corruption case. In the practice of discussion, the ideology can be conveyed and accepted well by society. As for the analysis of socio-cultural practices, the issue of corruption conducted by the supreme court judge and other corruption cases in 2013 had a major role in creating Catatan Najwa: “Trias Koruptika”.